Pesticidal Use and a Self-protective Behavior among Flower Agriculturists at Wangluek Subdistrict, Samchuk District, Suphanburi Province - ม่วงงาม นุชิตา; สุธีประเสริฐ ธานินทร์; ทองนาค ธนิฏฐา; เอี่ยมระหงษ์ วิโรจน์; สุนทร สุรศักดิ์ (Journal of Health Science of Thailand, 2021)
Nowadays, some agriculturists still have incorrect behavior of using agriculturally chemical substances with no proper protection. Thus, this is absolutely risky to directly contact and being jeopardized from such chemical substances. This survey research was aimed to explore pesticidal use and a self-protective behavior of flower agriculturists at Wangluek Subdistrict, Samchuk District, Suphanburi Province. The population of this study comprised 75 households with one participant represented one household. Data were collected by questionnaire and were analyzed by descriptive statistics, including frequency, percentage, mean, standard deviation, median, quartile deviation, minimum and maximum. Results showed that 25.33% of marigold agriculturists, 17.33% of jasmine agriculturists and 57.33% of crown flower agriculturists. In terms of gender, 68.00% were female with the age of 57 years old (Q.D.=5.00). 82.67% of the participants completed no higher than primary school level and had 30,000 Baht income. Demography for crown flower and jasmine agriculturists included age, education background and average annual income were not much different. However, the marigold agriculturist seemed to include the new generations with higher education and average annual income. Insecticides and growth regulator chemical substances were at the high level in the process of planting and harvesting. In addition, using such substances for marigold was lower than other flowers, yet the frequency of use was the highest. Agriculturists in three groups displayed high level of a self-protective behavior from pesticidal use. However the jasmine agriculturists and crown flower agriculturists still experiencing acute allergic reactions from pesticidal use. Future research should be focusing more upon promoting a better self-protective behavior towards pesticidal use in flower farming among agriculturists and agriculturists, s family.